Women at high risk of breast cancer: Molecular characteristics, clinical presentation and management - Kleibl, Zdenek; Kristensen, Vessela N (Breast (Edinburgh, Scotland), 2016)
The presence of breast cancer in any first-degree female relative in general nearly doubles the risk for a proband and the risk gradually increases with the number of affected relatives. Current advances in molecular oncology and oncogenetics may enable the identification of high-risk individuals with breast-cancer predisposition. The best-known forms of hereditary breast cancer (HBC) are caused by mutations in the high-penetrance genes BRCA1 and BRCA2. Other genes, including PTEN, TP53, STK11/LKB1, CDH1, PALB2, CHEK2, ATM, MRE11, RAD50, NBS1, BRIP1, FANCA, FANCC, FANCM, RAD51, RAD51B, RAD51C, RAD51D, and XRCC2 have been described as high- or moderate-penetrance breast cancer-susceptibility genes. The majority of breast cancer-susceptibility genes code for tumor suppressor proteins that are involved in critical processes of DNA repair pathways. This is of particular importance for those women who, due to their increased risk of breast cancer, may be subjected to more frequent screening but due to their repair deficiency might be at the risk of developing radiation-induced malignancies. It has been proven that cancers arising from the most frequent BRCA1 gene mutation carriers differ significantly from the sporadic disease of age-matched controls in their histopathological appearances and molecular characteristics. The increased depth of mutation detection brought by next-generation sequencing and a better understanding of the mechanisms through which these mutations cause the disease will bring novel insights in terms of oncological prevention, diagnostics, and therapeutic options for HBC patients.
Keywords: mutace; Tumor Suppressor Protein p53; Fanconi Anemia Complementation Group N Protein; Nuclear Proteins; nádory prsu; Genes, BRCA2; Female; biologické markery; jaderné proteiny; Biomarkers; Penetrance; ženské pohlaví; CD antigeny; nádorové supresorové proteiny; lidé; Checkpoint Kinase 2; geny BRCA2; AMP-Activated Protein Kinase Kinases; fosfohydroláza PTEN; Breast Neoplasms; Protein Serine-Threonine Kinases; Mutation; genetická predispozice k nemoci; ATM protein; Genetic Predisposition to Disease; Hereditary breast cancer; checkpoint kinasa 2; PTEN Phosphohydrolase; geny BRCA1; Risk Factors; Antigens, CD; Tumor Suppressor Proteins; nádorový supresorový protein p53; rizikové faktory; Ataxia Telangiectasia Mutated Proteins; Cadherins; kinasy AMP aktivovaných proteinkinas; penetrance; Breast cancer; Genes, BRCA1; kadheriny; protein-serin-threoninkinasy; protein FANCN; Breast cancer risk; Humans